Association between brain-muscle-ARNT-like protein-2 (BMAL2) gene polymorphism and type 2 diabetes mellitus in obese Japanese individuals: A cross-sectional analysis of the Japan Multi-institutional Collaborative Cohort Study. Issue 3 (December 2015) - Yamaguchi, Miwa; Uemura, Hirokazu; Arisawa, Kokichi; Katsuura-Kamano, Sakurako; Hamajima, Nobuyuki; Hishida, Asahi; Suma, Shino; Oze, Isao; Nakamura, Kazuyo; Takashima, Naoyuki; Suzuki, Sadao; Ibusuki, Rie; et al.
Highlights: This is a cross-sectional study among 35–69-year-old Japanese individuals. We examined BMAL genotype–environment (obesity) interactions in type 2 diabetes. BMAL2 rs7958822 genotype is associated with type 2 diabetes in obese men and women. An interaction between BMAL2 rs7958822 genotype and obesity was observed in men. Abstract: Aims: Brain-muscle-Arnt-like protein-1 ( BMAL1 ) and BMAL2 genes are essential components of the circadian clock, and are considered to be involved in glucose homeostasis. We examined whether single nucleotide polymorphisms (SNPs) of BMAL1 and BMAL2 were associated with the prevalence of type 2 diabetes (T2DM) in the general Japanese population. Methods: We studied 2467 subjects (1232 men and 1235 women, 35–69 years old), including 105 men and 57 women with T2DM, from the participants of the Japan Multi-institutional Collaborative Cohort Study. The association between SNPs in the BMAL1 (rs11022775 and rs2290035) and BMAL2 (rs7958822) genes and T2DM were analyzed by multiple logistic regression after adjustment for potential confounders. Analysis was also performed after stratification by body mass index (≥25 kg/m 2 and <25 kg/m 2 ) to investigate an interaction between genotypes and obesity. Results: The A/G and A/A genotypes of BMAL2 rs7958822 showed significantly higher adjusted odds ratios (OR) for T2DM than the G/G genotype among obese men (OR = 2.2, 95% confidence intervals [CI] 1.1, 4.6, P for interaction = 0.0495) and obese women (OR = 2.7, 95% CI 1.1, 6.7, P for interaction = 0.199). There were no significant associations between BMAL1 rs11022775 or rs2290035 genotypes and T2DM. Conclusions: To the best of our knowledge, this is the first study to show the significant association between BMAL2 rs7958822 genotype and T2DM among obese subjects.